2018
DOI: 10.1186/s12885-018-4807-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a frailty index in older cancer patients with solid tumours

Abstract: BackgroundFrailty is an indicator of physiological reserve in older people. In non-cancer settings, frailty indices are reliable predictors of adverse health outcomes. The aims of this study were to 1) derive and validate a frailty index (FI) from comprehensive geriatric assessment (CGA) data obtained in the solid tumour chemotherapy setting, and 2) to explore whether the FI-CGA could predict chemotherapy decisions and survival in older cancer patients with solid tumours.MethodsProspective cohort study of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
(26 reference statements)
1
33
0
Order By: Relevance
“…Although our findings support the use of frailty screening in patients with newly diagnosed PDAC, these assessments are not widely used to determine treatment plans. McCarthy et al used a frailty index to predict chemotherapy outcomes in older patients with cancer. They found that patients who were not assigned treatment were significantly more frail than were patients who completed chemotherapy or ones who discontinued chemotherapy prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings support the use of frailty screening in patients with newly diagnosed PDAC, these assessments are not widely used to determine treatment plans. McCarthy et al used a frailty index to predict chemotherapy outcomes in older patients with cancer. They found that patients who were not assigned treatment were significantly more frail than were patients who completed chemotherapy or ones who discontinued chemotherapy prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by age-associated factors, such as frailty, and other biological and prognostic factors [3][4][5][6][7][8][9]. Frailty is a collective deterioration of multiple physical and physiological functions yielding a lower tolerance of stressors such as cancer and treatments [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of frailty index is that each deficit should be health-related and increase with age. 24) Previous studies used 30-70 deficits to construct frailty indices. However, Searle et al 23) recommended that frailty indices should include at least 30-40 total deficits.…”
Section: Discussionmentioning
confidence: 99%
“…In general, missing variables can be imputed or removed from the denominator. 24 ) This study followed the latter approach of scoring KFI-PC. The KFI-PC score of each participant was calculated by dividing the number of deficits by the number of total variables that were recorded for that patient.…”
Section: Methodsmentioning
confidence: 99%